2018
DOI: 10.5664/jcsm.6974
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Randomized Sleep Education Intervention for College Students

Abstract: A brief and personalized online sleep education intervention improved sleep behaviors, sleep quality, and depressions scores. This novel approach to address sleep deprivation, poor sleep habits, and mood among college students may offer an effective and inexpensive remedy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 51 publications
5
54
0
2
Order By: Relevance
“…The Pittsburgh index (PSQI) has been used to assess sleep quality in adults for many years [ 27 ]. In our results, the students obtained scores above five in the pre-lockdown stage and scores above six in the post-lockdown stage, in line with recent studies that reported PSQI scores higher than 5 in 85% of subjects, which is considered pathological [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…The Pittsburgh index (PSQI) has been used to assess sleep quality in adults for many years [ 27 ]. In our results, the students obtained scores above five in the pre-lockdown stage and scores above six in the post-lockdown stage, in line with recent studies that reported PSQI scores higher than 5 in 85% of subjects, which is considered pathological [ 28 ].…”
Section: Discussionsupporting
confidence: 91%
“…Sleep hygiene education, cognitive behavioral therapy (CBT), relaxation, mindfulness, and hypnotherapy are effective strategies to improve sleep among higher education students [ 105 , 106 , 107 ]; thus, universities should consider incorporating these strategies to improve sleep quality of these students. One systematic review indicated increased effectiveness of CBT compared to other interventions in improving sleep quality and duration [ 107 ], and another systematic review showed that online CBT for insomnia is effective in improving sleep quality and duration among adults with chronic insomnia by identifying and modifying factors that contribute to poor sleep, including stress [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of strategies can be adopted by universities to improve students’ sleep, including sleep hygiene education [ 122 , 123 ], cognitive behavioral therapy for insomnia (CBTi), relaxation, mindfulness and hypnotherapy [ 124 ]. CBTi is an intervention that involves cognitive, behavioral and educational interventions [ 125 ].…”
Section: Discussionmentioning
confidence: 99%